The magnate family of Buczacki-Jazłowiecki, Moldavia in the fifteenth and sixteenth centuries and their unknown branch: Moldavian nobility of Buceațchi - Rezachevici, Constantin (Balcanica Posnaniensia. Acta et studia, 2009)
The article by Constantin Rezachevici explores the political and familial connections between the Buczacki-Jazłowiecki magnate family and Moldavia during the fifteenth and sixteenth centuries, highlighting their role in Polish-Moldavian relations. The study is set in the historical context of the Polish Crown’s southern border with Moldavia, established since the reign of Casimir the Great, when the Dniester River served as a natural frontier. Within this framework, the magnates of Podolia and Red Ruthenia, acting on behalf of the Polish king, played a crucial role in border politics and in maintaining diplomatic contacts with Moldavian rulers. The aim of the research is to reconstruct the history of the Buczacki-Jazłowiecki family, bearing the Abdank coat of arms, and to identify their previously unknown Moldavian branch—the boyar family of Buceațchi. Rezachevici employed a wide range of sources – Polish, Romanian, Latin, and Slavic – including archival documents, chronicles, and genealogical records. The research methodology is based on critical comparative analysis, allowing for verification and revision of earlier Polish and Romanian historiographical interpretations. The findings demonstrate that members of the Buczacki family held key administrative and military positions in Podolia and acted as royal envoys in negotiations with Moldavian rulers such as Alexander the Good, Stephen II, and Stephen the Great. The author also identifies a collateral branch of the family that settled in Moldavia in the fifteenth century, giving rise to the Buceațchi boyar family, documented up to the seventeenth century. Rezachevici concludes that the Buczacki-Jazłowiecki family served as vital intermediaries between Poland and Moldavia and significantly contributed to shaping the political and cultural history of the borderland. This study offers a valuable contribution to the understanding of shared Polish-Romanian heritage.